Fundamentals of Collection Development and Management (Review) - Thomas, William Joseph (East Carolina University, 2010)
Book review of the second edition of Peggy Johnson's Fundamentals of Collection Development and Management (ALA, 2010).
Keywords: Collection development (Libraries); Academic libraries